Circulating metals, leukocyte microRNAs and microRNA networks: A profiling and functional analysis in Chinese adults. (November 2022) - Li, Wending; Xu, Xuedan; Jiang, Qin; Long, Pinpin; Xiao, Yang; You, Yutong; Jia, Chengyong; Wang, Wei; Lei, Yanshou; Xu, Jianjian; Wang, Yufei; Zhang, Min; et al.
Highlights: In Chinese adults, 9 circulating metals were significantly associated with 55 leukocyte miRNAs. Ni-Pb-V were positively associated with 5 lymphocyte-enriched miRNAs inhibiting DNA repair. Ni-Pb-V were inversely associated with 4 granulocyte-enriched miRNAs promoting DNA repair. Metal-associated miRNAs may modulate immune function as networks in a cell type specific manner. Abstract: Background: Metals in the human body represent both environmental exposure and nutritional status. Little is known about the miRNA signature in relation to circulating metals in humans. Objectives: To characterize metal-associated miRNAs in leukocytes, individually and collectively as networks. Methods: In a panel of 160 Chinese adults, we measured 23 metals/metalloids in plasma, and sequenced miRNAs and mRNAs in leukocytes. We used linear regression to model the associations between ln-transformed metal concentrations and normalized miRNA levels adjusting for potential confounders. We inferred the enriched leukocyte subtypes for the identified miRNAs using an association approach. We utilized mRNA sequencing data to explore miRNA functions. We also constructed modules to identify metal-associated miRNA networks. Results: We identified 55 metal-associated miRNAs at false discovery rate-adjusted P  < 0.05. In particular, we found that lead, nickel, and vanadium were positively associated with potentially lymphocyte-enriched miR-142-3p, miR-150-3p, miR-28-5p, miR-361-3p, and miR-769-5p, and were inversely associated with potentially granulocyte-enriched let-7a/c/d-5p and miR-1294. Interestingly, the five lymphocyte-enriched miRNAs inhibited, whereas miR-1294 activated, ROS and DNA repair pathways. We further confirmed the findings using oxidative damage biomarkers. Next, we clustered co-expressed miRNAs into modules, and identified four miRNA modules that were associated with different metals. The identified modules represented miRNAs enriched in different leukocyte subtypes, and were involved in biological processes including hematopoiesis and immune response, mitochondrial functions, and response to the stimulus. Conclusions: At commonly exposed low levels, circulating metals were associated with distinct miRNA signatures in leukocytes. The identified miRNAs, individually or as regulatory networks, may provide a mechanistic link between metal exposure and pathophysiological changes in the immune system.